근시성 맥락막 신생혈관 환자에서 스펙트럼 영역 빛간섭단층촬영으로 측정한 맥락막 - 박진성; Jin Sung Park; 조영욱; Young Wook Cho; 장지혜; Ji Hye Jang (Daihan angwa haghoi jabji, 2014)
목적: 스펙트럼영역 빛간섭단층촬영을 이용하여 근시성 맥락막신생혈관 환자에서 신생혈관이 발생한 부위의 맥락막이 주변부 맥락막과 어떤 차이가 있는지 알아보고자 한다. 대상과 방법: 근시성 맥락막신생혈관을 가진 환자 19명에서 신생혈관이 있는 부위를 1군, 그 주변부를 2군으로 정의하고, 대조군으로 반대안의 중심와 부위를 3군으로 정하여 후향적 연구를 시행하였으며, 빛간섭단층촬영으로 맥락막 두께와 맥락막 대혈관의 직경을 측정하여 비교 분석하였다. 결과: 맥락막 두께는 1군 80.00 ± 68.31, 2군 63.44 ± 67.75, 3군 71.11 ± 65.69 μm였다. 1군은 2군에 비해 유의하게 두껍게 관찰되었고(p=0.038), 1군과 3군, 2군과 3군은 유의한 차이를 보이지 않았다(p=0.365, p=0.314). 맥락막 대혈관 직경은 1군 57.47 ± 39.78, 2군 40.45 ± 34.69, 3군 45.63 ± 37.00 μm였다. 1군은 2군에 비해 유의하게 크게 관찰되었고(p=0.025), 1군과 3군, 2군과 3군은 유의한 차이를 보이지 않았다(p=0.123, p=0.325). 결론: 근시성 맥락막신생혈관 환자에서 맥락막신생혈관이 발생한 부위의 맥락막 두께, 맥락막 대혈관 직경이 맥락막신생혈관 주변부에 비해 큰 것을 알 수 있었다. 이는 비록 맥락막신생혈관이 맥락막혈관의 위축에 의한 외측망막의 허혈 자극에 의해 발생하지만, 맥락막신생혈관이 발생하는 부위는 어느 정도의 맥락막의 두께 및 맥락막 대혈관 직경이 유지되어 있음을 보여준다고 생각한다. <대한안과학회지 2014;55(9):1313-1319> Purpose: Using the spectral domain optical coherence tomography (SD-OCT), we studied the difference in the choroida morphology between the choroidal neovascularization (CNV) area and the area surrounding CNV. Methods: This retrospective study consisted of 19 patients with myopic CNV lesion in eye; fellow eyes were used as controls. All eyes were analyzed by measuring the choroidal thickness and large choroidal vessel size using SD-OCT. Eyes with CNV were divided into groups; the neovascular lesion was defined as group 1, the surrounding area as group 2. Subfovea of the fellow eye was defined as group 3. Results: The choroidal thickness was 80.00 ± 68.31 in group 1, 63.44 ± 67.75 in group 2 and 71.11 ± 65.69 μm in group 3. There was a significant difference between group 1 and group 2 (p = 0.038). There were no significant differences between group 1 and 3 or between group 2 and 3 (p = 0.365, p = 0.314). The large choroidal vessel size was 57.47 ± 39.78 in group 1, 40.45 ± 34.69 in group 2 and 45.63 ± 37.00 μm in group 3. There was a significant difference between group 1 and group 2 (p = 0.025). There were no significant differences between group 1 and 3 or between group 2 and 3 (p = 0.123, p = 0.325). Conclusions: Choroidal thickness and large choroidal vessel size at the center of the CNV were greater than in the area surrounding CNV. The results suggest that although the CNVs were due to a thinned choroid caused by severe choroidal ischemia, the development of CNV requires maintenance of choriocapillaris and large choroid vessels. J Korean Ophthalmol Soc 2014;55(9):1313-1319